PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BUMI MINERAL SULAWESI - M. Farhan; Muhammad Kasran; Suparni (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to determine and analyze the relationship between leadership style and work environment with employee performance at PT Bumi Mineral Sulawesi. This study used 70 respondents as samples. The hypothesis was tested using multiple linear regression analysis using the SMART PLS application. The results showed that leadership style and work environment have a significant positive influence on employee performance at PT. BUMI MINERAL SULAWESI Keywords: leadership style, work environment, and employee performance